The Influence of Islamic Work Ethic, Motivation, and Work Environment on Employee Performance at Muslimah Beauty Salon in Samarinda - Faadhilah, Rifdah; Norvadewi, Norvadewi; Parlina, Tika; Zaroni, Akhmad Nur (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2022)
Human resources are a crucial factor in achieving targets and goals in business. One of the businesses overgrowing today is the Muslim beauty salon business. Employees mainly support the success of this business with good performance. However, employee performance is influenced by various factors. This study aims to determine the influence of Islamic work ethic, motivation, and environment on employee performance at the Muslimah beauty salon in Samarinda. This study is a quantitative study with a study population of 15 employees. Data collection techniques use questionnaires and documentation, while data analysis uses multiple regression analysis. The study's results found that motivation affects the performance of employees in the Muslimah beauty salon in Samarinda. However, Islamic work ethic and environment have no bearing on employee performance. Simultaneously, Islamic work ethic, motivation, and work environment influenced employee performance at the Muslimah beauty salon in Samarinda with an influence of 78.6%. Other factors outside this study influenced the remaining 21.4%.